Measuring Specificities of Dissipation Factor of Electrical Equipment in Substations - Gavrilovs, Gerards; Vītoliņa, Sandra (Electrical, Control and Communication Engineering, 2010)
Measuring techniques of dielectric losses tanδ of high voltage equipment are discussed and compared in this paper. There are several methods for determining tanδ and capacitance values in high voltage substation on site.Simple measuring methods like GST and UST can be put into practice without result corrections in ideal conditions. However electrical field in substation originates negative affect on measuring results, therefore different connection schemes of measuring methods have to be used.